FORMAÇÃO INICIAL EM PEDAGOGIA E APRENDIZAGEM DOCENTE: NARRATIVAS DE PROFESSORES DOS ANOS INICIAIS DE ESCOLAS DE SANTA MARIA, RS - Pasetto, Luciane Zamberlan (2019)
The aim of this study was to investigate how Pedagogy training has an impact on the teaching learning of teachers in the early years of elementary school. Specifically, the objective was to analyze aspects related to initial and continuing education, as well as skills and competences developed in the professional career of teachers of the early years; analyze the process of teacher education and its contributions in the formation of a teacher of the early years; and analyze the motivation for teaching and professional satisfaction of the research participants. The sample consisted of nine (9) teachers trained in Pedagogy, who work from the early years, in public or private schools in Santa Maria, RS. The methodology is a qualitative approach, centered on the interviewees' life history narratives. For data collection, a form for personal data records and a narrative interview recorded in audio were used. The analysis, supported by the technique of Discursive Textual Analysis (ATD), by Moraes and Galiazzi (2007), shows that, in the professional choice, some participants came into conflict with family members, but nevertheless realized the dream of being a teacher. This conflict was due to the fact that family members wanted them to pursue more profitable professions than teaching. The results are presented in three complementary articles in which the following findings were obtained: in Article 1, from the narratives of the participants' personal trajectory, the interlocutions between the initial education in Pedagogy and the continuing education are discussed; In Article 2 we report the path of a teacher of the Early Years and it is inferred that his experiences of family, school and academic daily life were fundamental in his teacher education and professionalization; In Article 3, it is shown how the motivation for teaching originates in family stimulation and in teachers who served as an example, which results from professional satisfaction. The section called discussion of the study can be understood as an integrative synthesis of the three articles, articulating the research results. Therefore, this study presents an innovative perspective in the understanding of the teaching trajectory of the participants. The narratives made it possible to understand how teaching motivation and job satisfaction go hand in hand, as well as the difficulties encountered by teachers are also motivating the search for a better practice. Students who are discouraged by their behavior towards the teacher, also present themselves as a source of motivation for them. It is concluded that the challenges of the teaching profession are notorious and call for changes to improve teaching.